Enzymatic Synthesis of Hydroxycinnamic Acid Amides in Water Using the Promiscuous Hydrolase/Acyltransferase PestE from Pyrobaculum calidifontis VA1 - Baumert, Benjamin; Terholsen, Henrik; Cziegler, Clemens; Thier, Isabel; Badenhorst, Christoffel P. S.; Siems, Karsten; Bornscheuer, Uwe T. (Synlett, 2024)
Hydroxycinnamic acid amides are believed to have antioxidant, antidiabetic, cytotoxic, anticancer, neuroprotective, and antiinflammatory properties, making them interesting target molecules for potential applications in the food, cosmetics, and pharmaceutical industries. Here, we describe the synthesis of hydroxycinnamic acid amides starting from hydroxycinnamic acid esters and the corresponding amines by using variants of the promiscuous hydrolase/acyltransferase from Pyrobaculum calidifontis VA1 (PestE) in water as a solvent. Up to 97% conversion within two hours at 60 °C was achieved with methyl ferulate and tyramine as substrates. This is a promising, environmentally friendly alternative strategy to established chemical synthesis routes or enzymatic methods using lipases in nonaqueous organic solvents.
Keywords: acyltransferase; amides; biocatalysis; carboxylesterase; hydroxycinnamic amides